Effectivity and economical aspects for agile quality assurance in large enterprises. Issue 11 (25th October 2016) - Poth, Alexander
Abstract: The transition from a classical to an agile software development procedure needs a structured and strategic roll out to realize the expected benefits of the transition phase. Quality assurance as part of the software development has also to be designed to realize its targets of the agile transition for adequate project and program quality assurance. Besides effectivity the economic aspects have to be implemented also in a value‐driven agile product quality assurance. This tension between effectivity and economy will be shown on the example of the Volkswagen group IT. The transition is mapped to the SPI Manifesto to demonstrate the currency in 2009 of the established values and principles for software process improvement. Abstract : The transition from a classical to an agile software development procedure needs a structured and strategic roll out to realize the expected benefits of the transition phase. Quality assurance as part of the software development has also to be designed to realize its targets of the agile transition for adequate project and program quality assurance. Besides effectivity, the economic aspects have to be implemented also in a value‐driven agile product quality assurance.